2007
DOI: 10.1113/jphysiol.2006.122135
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced macroscopic desensitization shapes the response of α4 subtype‐containing GABAA receptors to synaptic and extrasynaptic GABA

Abstract: Up-regulation of the GABA A receptor α4 subunit subtype has been consistently shown in multiple animal models of chronic epilepsy. This isoform is expressed in both thalamus and hippocampus and is likely to play a significant role in regulating corticothalamic and hippocampal rhythms. However, little is known about its physiological properties, thus limiting understanding of the role of α4 subtype-containing GABA A receptors in normal and abnormal physiology. We used rapid GABA application to recombinant GABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 60 publications
10
88
2
Order By: Relevance
“…α3-containing receptors had the slowest activation rate, while the other receptor isoforms all had activation rates near 1 ms. The slow activation of α3 receptors has been found in previous studies (Gingrich et al, 1995), although our results show faster rates than others have found for α1-and α4-containing receptors (McClellan and Twyman, 1999;Lagrange et al, 2007). The slow activation rate associated with the α3 subtype could also influence our ability to accurately measure the GABA EC 50 and to detect fast components of desensitization for these receptors.…”
Section: Effect Of α Subtype On Activation Ratesupporting
confidence: 52%
See 2 more Smart Citations
“…α3-containing receptors had the slowest activation rate, while the other receptor isoforms all had activation rates near 1 ms. The slow activation of α3 receptors has been found in previous studies (Gingrich et al, 1995), although our results show faster rates than others have found for α1-and α4-containing receptors (McClellan and Twyman, 1999;Lagrange et al, 2007). The slow activation rate associated with the α3 subtype could also influence our ability to accurately measure the GABA EC 50 and to detect fast components of desensitization for these receptors.…”
Section: Effect Of α Subtype On Activation Ratesupporting
confidence: 52%
“…It is also possible that the relatively slow application rate associated with the whole-cell recording configuration could influence our ability to accurately capture the peak current, and therefore alter the measured EC 50 . In addition, the disruption of interactions of the receptor with cytoskeletal proteins through the process of patch excision could also alter channel properties and could result in differences between whole-cell and outside-out patch recordings (Chen and Olsen, 2007;Lagrange et al, 2007).…”
Section: Deactivation Rate -5 Msec Gaba Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This alteration has been hypothesized to be proepileptic because (1) epileptogenic insults (lithium-pilocarpine treatment) increase the α1 subunit expression in immature rats, which are less susceptible than adults to the development spontaneous seizures (28); (2) the α1 subunit is significantly more expressed in slowkindling than in fast kindling rats (29); (3) viral vector-mediated correction of the alteration in the α1/α4 ratio inhibits epilepsy development in the pilocarpine model (30). Interestingly, a recent study (31) shows that α4-containing GABA A channels possess characteristics that imply a reduced GABA response to high frequency stimulation: reduced activation rate, prolonged desensitization, reduced response to repetitive GABA application (i.e., increased run-down). None of these studies, however, describes the evolution of these molecular changes with the natural history of the disease and their correlation with the appearance and maintenance of increased run-down.…”
Section: Resultsmentioning
confidence: 99%
“…Recording and Analysis of Macroscopic GABA Evoked Currents-As described before (17) Ϫ equilibrium potential across the cell membrane was close to zero with the combination of external and internal solutions. Cells were voltage-clamped at Ϫ20 mV using an Axopatch 200A amplifier (Axon Instrument).…”
Section: Glycomic Profiling Of N-glycans Of Surface ␤2 Subunits With mentioning
confidence: 99%